2021
DOI: 10.3390/molecules26082284
|View full text |Cite
|
Sign up to set email alerts
|

Laguncularia racemosa Phenolics Profiling by Three-Phase Solvent System Step-Gradient Using High-Performance Countercurrent Chromatography with Off-Line Electrospray Mass-Spectrometry Detection

Abstract: The detailed metabolite profiling of Laguncularia racemosa was accomplished by high-performance countercurrent chromatography (HPCCC) using the three-phase system n-hexane–tert-butyl methyl ether–acetonitrile–water 2:3:3:2 (v/v/v/v) in step-gradient elution mode. The gradient elution was adjusted to the chemical complexity of the L. racemosa ethyl acetate partition and strongly improved the polarity range of chromatography. The three-phase solvent system was chosen for the gradient to avoid equilibrium problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The BPC major compound Ac M1 ( Figure S7 ) might be myricetin-3-glucoronid ( Figure S2a ), found in the leaves of mangrove Conocarpus erectus [ 42 ]. The BPC major compound Ac M2 ( Figure S8 ) could be a quercetin glucuronide already described in Laguncularia racemosa [ 43 ], while the BPC major compound Ac M3 ( Figure S9 ) could be kaempferol-3-glucoside, also known as astragalin ( Figure S2b ). Vinh et al, 2019 reported this metabolite in A. corniculatum leaves, supporting our assumptions [ 41 ].…”
Section: Resultsmentioning
confidence: 79%
“…The BPC major compound Ac M1 ( Figure S7 ) might be myricetin-3-glucoronid ( Figure S2a ), found in the leaves of mangrove Conocarpus erectus [ 42 ]. The BPC major compound Ac M2 ( Figure S8 ) could be a quercetin glucuronide already described in Laguncularia racemosa [ 43 ], while the BPC major compound Ac M3 ( Figure S9 ) could be kaempferol-3-glucoside, also known as astragalin ( Figure S2b ). Vinh et al, 2019 reported this metabolite in A. corniculatum leaves, supporting our assumptions [ 41 ].…”
Section: Resultsmentioning
confidence: 79%
“…Their approach employed a quick ultra-performance liquid chromatography under voltage (UPLC-UV) method to qualitatively and quantitatively analyze four glycoside isomers found in the leaves of Idesia polycarpa maxim. They examined and validated the chemical characteristics of those isomers using various analytical tools such as UV, UPLC, Fourier-transform infrared, ESI-MS, 1 H-NMR, 13 C-NMR, and 2D-NMR spectra [57,70,75,85].…”
Section: Flavonoid and Phenolic Compoundsmentioning
confidence: 99%